Peran TPQ Al-Barokah Bandengan Dalam Mengembangkan Minat Baca Tulis Al-Qur’an Melalui Pendidikan Non-Formal - Amalia, Yudria; Saefudin, Ahmad (Universitas Muhammadiyah Ponorogo, 2026)
The main objective of this study is to thoroughly examine how Taman Pendidikan Al-Qur'an (TPQ) Al Barokah Bandengan improves children's interest in reading and writing Al- Qur'an, especially in light of problems in the digital age. Nonformal religious education like TPQ has to compete fiercely with contemporary media, hence teaching techniques must be updated. The main finding of this study reveals that good teacher-parent cooperation is essential for successfully fostering such interest. Although teachers serve as facilitators, motivators, and providers of a well-organized curriculum (by means of methods such Iqra' or Wafa, as well as a rewards system), parents' role is considered much more crucial as the main driver of success. Parents are responsible for the constant conservation provided at home and lead by example. Sebenarnya dari kurang perhatian, kesibukan, atau sikap acuh tak acuh orang tua; dan dampak buruk dari anak bergantung pada gawai which could hamper interest and focus in school is where the greatest challenges arise. To meet that challenge, the most effective and enjoyable solutions are stress on visualisations (such as utilizing a colored blackboard to teach tajwid) and implementation of an Interractive Learning Approach (like peer teaching or couple learning). Drawing student attention, simplifying material comprehension, and generating a collaborative and intriguing learning environment are all advantages of this strategy. Overall, this study emphasizes that in order to develop an effective modern model for teaching the Al- Qur'an in TPQ, it is quite vital to reinforce collaboration by way of regular evaluation and the creation of enjoyable, adaptive learning strategies that make use of elements of competition and prize as drivers of interest in studies